Performances of dye-sensitized solar cell (DSSC) with working electrode of aluminum-doped ZnO nanorods - Truly Theresia Saputrina; Iwantono Iwantono; Awitdrus Awitdrus; Akrajas Ali Umar (Science, Technology, and Communication Journal, 2020)
Renewable energy sources are intensively developed for substituting fossil energy by several routes, such as solar cells and wind power. As a kind of solar cell, dye-sensitized solar cell (DSSC) was studied for low cost and environmentally friendly cell in competing with a silicon-based cell which dominated in the market. But, main problem in DSSC is low current density and power conversion efficiency, especially zinc oxide (ZnO)-based DSSC. In this paper, we enhance the ZnO nanorod properties through the doping of aluminum (Al). For obtaining optimum results, we varied the dopant concentration of 1%, 1.5%, 1%, and 3%. The Al-doped ZnO nanorod was grown by a seed-mediated hydrothermal method at 90oC for 8 hours. The physical properties were analyzed by field emission scanning electron microscopy and EDX, while the photovoltaic properties were analyzed by J-V curve analysis. An improvement of photovoltaic performance up to 200% is obtained by the ZnO nanorod with 1% Al-doped concentration.